A Prospective Study in the Evaluation of Quality of Life After Vulvar Cancer Surgery. Issue 1 (January 2015) - Novackova, Marta; Halaska, Michael J.; Robova, Helena; Mala, Ivana; Pluta, Marek; Chmel, Roman; Rob, Lukas
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to prospectively monitor the patients' quality of life (QoL) after vulvar cancer surgery. Design The design was prospective clinical study. Setting The study was set in the Department of Obstetrics and Gynecology, 2nd Medical Faculty of the Charles University and University Hospital Motol, Prague, Czech Republic. Methods A group of 36 patients underwent vulvar cancer surgery: 24 patients were subject to inguinofemoral lymphadenectomy (RAD) and 12 to sentinel lymph node biopsy. To evaluate QoL, the European Organisation for Research and Treatment of Cancer, QoL questionnaires (QLQ-C30 and QLQ-CX24) were administered to patients before and 6 and 12 months after surgery. Results In patients with vulvar cancer after inguinofemoral lymphadenectomy, increased fatigue and impaired lymphedema were observed. In the group of patients after sentinel lymph node biopsy, none of the QoL variables worsened postoperatively. Comparing both groups 12 months after surgery, the RAD group had significantly worse outcomes in body image and cognitive functioning than the sentinel lymph node biopsy group. Patients in the RAD group, who received adjuvant radiotherapy (n = 13), had worse QoL in symptom experience (P < 0.05) at 6 and 12 months after the surgery than patients without radiotherapy (n = 11). Conclusions Less radical surgery showed objectively better QoL results.